PEMBUBARAN PARTAI POLITIK DALAM SISTEM KETATANEGARAAN INDONESIA - Widayati Widayati (Unissula, 2011)
Indonesia is a sovereign country folk. One implementation of the sovereignty of the people is the election that followed by political parties for members of Parliament and members of parliament and individuals for DPD.Political parties are the main pillars of democracy. Establishment of political parties must meet the requirements in accordance with legislation. Terms of founding a political party regulated under Article 2 of Law No. 2 of 2008 on Political Parties.As the main pillar of democracy, political parties should be able to carry out its functions properly. There are some restrictions on political parties, among others, are prohibited from engaging in activities contrary to the Constitution of 1945 NRI and legislation; engage in activities that endanger the integrity and safety Homeland. If the ban is violated, then the government may ask the parties to the freezing of the District Court. If the parties do not accept the decision of freezing the District Court, it can be appealed to the Supreme Court. If the Supreme Court confirmed the decision of the PN, then the Government may propose the dissolution of the parties to the Court.The procedure by which parties to the Court daitur dissolution under Article 68 paragraph (1) and (2) of Law No 24 of 2003 on the Constitutional Court. Constitutional Court's decision regarding the request for the dissolution of political parties must be decided upon within a period of 60 (sixty) days after pemoohonan recorded in the Register of Case Constitution.Keywords: Parati dissolution of political, constitutional systemIndonesia